Exploring Hurdles Encountered by a Part-Time Female Teacher: A Gender-based Auto-ethnographic Perspective - Acharya, Milan (ILAM इलम, 2024)
The researcher, a female part-time teacher with eight years of experience serves as the main agency for data collection and analysis in this auto-ethnographic study. Auto-ethnography is based on its exceptional capacity to combine academic research and personal experiences, enabling a thorough examination of the researcher's path as a female part-time teacher at Tribhuvan University (TU). The study focuses on the gender-related obstacles that part-time female teachers on TU must overcome. Self-reflections, observations, insights, and the realities encountered throughout the researcher's eight-year stay are all included in the qualitative data gathering. The application of content analysis to self-reflection write-ups facilitates the interpretation and synthesis of recurrent patterns and insights, thereby advancing a nuanced comprehension of the gender-related obstacles faced by female part-time teachers. The findings show that female part-time teachers face many structural issues, such as a lack of institutional recognition of being female, unfair requests for academic and financial contributions, exploitation, and rejection from appointments despite having academic and research competency. The aforementioned issues highlight the necessity of extensive reforms within the university system to mitigate gender-based inequalities, guarantee equitable treatment, and cultivate a climate that is consistent with the values of professionalism and equality. This study adds insightful information to the continuing conversation on gender parity in higher education in Nepal.